Numerical integration algorithm potentially-streaming equations in lumped parameters to control the correctness of the approximate solution - Igor Evgenievich Starostin (Kompʹûternye issledovaniâ i modelirovanie (Online), 2014)
This work is devoted to development of an algorithm for numerical integration of differential equations potentially-streaming method simulation of non-equilibrium processes. This method was developed by the author in his earlier published works. In this paper, consideration is limited to systems with lumped parameters. Also previously developed method for analyzing the correctness of the author of the approximate solution of the system potentially-streaming equations for systems in lumped parameters. The purpose of this article is to combine this technique with modern numerical methods for integrating systems of ordinary differential equations and the development of methods of numerical integration of systems of equations potentially-streaming method that allows to guarantee the correctness of the approximate solution.